Evidence-Based Education: Faculty Development Workshop to Promote Critical Thinking Skills in Dental Education - Sophia Saeed (Association of American Medical Colleges, 2017)
Introduction The Commission on Dental Accreditation emphasizes the importance of teaching critical thinking. If faculty are expected to change the way they teach, training resources that employ the methods of promoting critical thinking must be made available to provide guidance on how to teach critical thinking. A search of MedEdPORTAL showed no peer-reviewed active learning resources for faculty development in the domain of critical thinking. Methods This 90-minute workshop is designed to provide preclinical and clinical dental faculty with strategies to promote critical thinking skills in their students. It includes a presentation on foundational knowledge about critical thinking and knowledge organization, followed by small- and large-group activities. Videos of real teaching encounters are reviewed so that different teaching styles can be seen and discussed. Results This workshop was given at the 2014 American Dental Education Association Annual Session, receiving an overall rating of 3.67 on a Likert-type scale of 1-4, with 4 being the highest score. It was repeated at the University of California, San Francisco School of Dentistry, where it received an overall rating of 4.7 on a Likert scale of 1-5, with 5 being the highest score. Discussion For faculty who learned in teacher-centered curricula, training may be necessary to provide them with skills for contemporary teaching in this new domain of competence. This workshop offers such training.